Jewelry box: Malaysian architecture / Khairul Syazwan Khairul Albar - Khairul Albar, Khairul Syazwan (2022)
Malaysian architecture is a complex fusion of Islamic style, colonial rule, and Asian traditions, best seen in Kuala Lumpur, the country's capital and largest metropolis. Malaysia's design frequently works with mediating internal and external space because of the country's humid island environment.